(untitled) (Research, Society and Development, 2021)
The discussion of the theme is necessary, mainly within the Psychology undergraduate courses, in order to equip the professional theoretically, so that they can deal with the issues that arise in practice. This article aims to report the experience of a psychological intervention performed on a patient who was in a suicide crisis, after an attempt. This report of professional experience has a qualitative nature. There is a need for the service to be marked by the therapist’s welcoming and empathetic posture, so that the patient feels supported. This type of intervention aims to provide support to the patient, establish safety measures for their physical integrity, reduce the risk of further attempt and make referrals to the necessary services.